Effect of friction modifiers compositions on tribological properties of Cu-Sn alloy/Al2O3 brake composite material. (August 2021) - Singh, Vaibhav; Raja, P; Katiyar, Jitendra Kumar; Ramkumar, P
Brakes are very important component in any vehicle, used to stop the motion of it either by applying mechanical or hydraulic pressure on brake pads. By engaging and disengaging of braking action, the surface of brake components (or) materials is ruined after some time. Therefore, it is important to study and develop a new composition of brake materials which provides optimum coefficient of friction along with increasing wear resistance to the materials. Hence, new combination has been formulated for fabrication of brake composite material using powder metallurgy method which consist of copper-tin alloy mixed with silicon carbide as a base materials, aluminium oxide as an abrasive material with varying volume percentage of graphite and talc powder as a friction modifiers. The pin-on-disc test was performed on brake composite material to analyse their tribological properties namely friction and wear. From tribo-test, it was observed that all composites give the friction coefficient in the range of ∼0.33–0.51 and the loss of materials in the range of ∼79–131 mg. Further, the mechanical, thermal stability and surface characterization were also carried out on brake composites using universal testing machine, vicker's hardness tester, thermogravimetric analyser and scanning electron microscope respectively. These results reveal a very marginal change in hardness, increase in compressive strength by increase of talc concentration to the matrix, uniform distribution of reinforcement into the matrix and multi stage degradation of material loss in thermograph.